Rhodium(III)‐Catalyzed Alkenylation–Annulation of closo‐Dodecaborate Anions through Double B−H Activation at Room Temperature. Issue 50 (15th November 2016) - Zhang, Yuanbin; Sun, Yuji; Lin, Furong; Liu, Jiyong; Duttwyler, Simon
Abstract: 1, 2, 3‐Trisubstituted closo ‐dodecaborates with B−O, B−N, and B−C bonds as well as a fused borane oxazole ring have been synthesized by rhodium‐catalyzed direct cage B−H alkenylation and annulation of ureido boranes in the first reported example of regioselective B−H bond functionalization of the [B12 H12 ] 2− cage by transition‐metal catalysis. This reaction proceeded at room temperature under ambient conditions and exhibited excellent selectivity for efficient monoalkenylation with good functional‐group tolerance. The urea moiety enabled B−H activation by acting as a directing group, was incorporated in the oxazole ring in situ, and also avoided multiple alkenylation. A possible mechanism is proposed on the basis of the isolation of a rhodium agostic intermediate and control experiments. Abstract : Let there B activation : 1, 2, 3‐Trisubstituted closo ‐dodecaborates with B−O, B−N, and B−C bonds were synthesized efficiently by rhodium(III)‐catalyzed double B−H activation of ureido boranes (see scheme). A possible mechanism for this regioselective B−H bond functionalization of the [B12 H12 ] 2− cage is proposed on the basis of the isolation of a rhodium intermediate and control experiments.